Evaluation on Website Based Program for Event-Based Surveillance by Sub - District Networks - ผาตินาวิน ลดารัตน์; มาตรา บุญโรม (Disease Control Journal, 2013)
The objective of this study was to assess the effectiveness of the implementation of web-based program for public health emergency events surveillance by sub-district networks. This program was composed of 4 main menu include event notify data and reporting and information of district SRRT members. Data was collected by using questionnaire which replied by 1279 users and reviewing database in website of the Bureau of Epidemiology. The results revealed that most of the users were convenient for events reporting 47.54 % , satisfied very much 49.41% and agree to use this program further 87.49%. The notified events were increase form 5,117 events in 2011 to be 33,270 events in 2012. The notified events were approved by health officers 23.28% in 2011 and 55.53% in 2012, respectively. More than 90% of total notified events were reasonable to be reported. However the evaluation and improvement of this program should be done continuously.